2015
DOI: 10.7448/ias.18.1.19445
|View full text |Cite
|
Sign up to set email alerts
|

What are the constraints and opportunities for HIVST scale‐up in Africa? Evidence from Kenya, Malawi and South Africa

Abstract: IntroductionHIV self-testing (HIVST) has the potential to increase uptake of HIV testing among untested populations in sub-Saharan Africa and is on the brink of scale-up. However, it is unclear to what extent HIVST would be supported by stakeholders, what policy frameworks are in place and how variations between contexts might influence country-preparedness for scale-up. This qualitative study assessed the perceptions of HIVST among stakeholders in three sub-Saharan countries.MethodsFifty-four key informant in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
80
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(86 citation statements)
references
References 35 publications
6
80
0
Order By: Relevance
“…Similar to this study, the findings of other scholars (Grésenguet, de Dieu Longo, Tonen-Wolyec, Bouassa, & Belec, 2017;van Rooyen et al, 2015) revealed a lack of information concerning the use of HIVST. The researchers noted the need for educational pictograms and notices to be in the vernacular language(s) to avoid the frequent difficulties faced with the use of HIVST and the frequent misinterpretation of the test results (Grésenguet et al, 2017).…”
Section: Discussionsupporting
confidence: 83%
“…Similar to this study, the findings of other scholars (Grésenguet, de Dieu Longo, Tonen-Wolyec, Bouassa, & Belec, 2017;van Rooyen et al, 2015) revealed a lack of information concerning the use of HIVST. The researchers noted the need for educational pictograms and notices to be in the vernacular language(s) to avoid the frequent difficulties faced with the use of HIVST and the frequent misinterpretation of the test results (Grésenguet et al, 2017).…”
Section: Discussionsupporting
confidence: 83%
“…Similar to this study, the ndings of other scholars [19,20] revealed a lack of information concerning the use of HIVST. The researchers noted the need for educational pictograms and notices to be in the vernacular language(s) to avoid the frequent di culties faced with the use of HIVST and the frequent misinterpretation of the test results [20].…”
Section: Discussionsupporting
confidence: 80%
“…The information materials constituted detailed instructions for use, linkage to care, and disposal of used testing swabs. Information on how to use HIVST kits alleviated misinterpretation and misconception of results, thus promoting intervention uptake [10,47]. Clearly labeled protected bins were placed in the testing room and in strategic points at the hostels for the purposes of disposal.…”
Section: Intervention Phasementioning
confidence: 99%
“…In Africa, delay in HIV/AIDS diagnosis contributes signi cantly to high rates of early mortality [6][7][8]. Barriers to the uptake of HTS include stigma concerns, fear of prognosis, diminished HIV risk awareness, and the inconvenience, transportation and opportunity costs incurred [9,10]. New client-centered approaches to testing such as 'self-testing' have recently been used to address some of these barriers [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%